Letramento científico expresso em histórias em quadrinhos elaboradas por sócios-mirins do clube de ciências da UFPA - Silva, Edson José Monteiro da (2024)
This work aims to analyze scientific literacy in its educational aspects, how it can be used to teach literacy to students in the early years, using comics taken from students from the Science Club of the Federal University of Pará. In this way, the educational and social benefits that a well-done scientific literacy process can bring to students will initially be discussed, to justify the importance of inserting, in a more incisive and categorical way, scientific literacy activities from the first years of literacy. from the students. Next, four comic books produced by junior members of the UFPA Science Club are presented and analyzed, produced to encourage them to demonstrate their scientific knowledge regarding bacteria and other agents that can attack the human body. We analyze in these stories how scientific literacy occurred and if it occurred, distinguishing it from pure and simple literacy.